PERBANDINGAN GAYA BAHASA PADA PUISI “IBU” KARYA MUSTOFA BISRI DENGAN LIRIK LAGU “KERAMAT” KARYA RHOMA IRAMA - Fahrudin Mualim (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2015)
Abstract: This study was aimed to describe the comparison of the figurative language of the poetry “Ibu” (Mother) by Mustafa Bisri and the lyric of the song